(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The methodological strategy used in this research was based on a mixed approach, combining qualitative and quantitative methods. The research design was non-experimental, cross-sectional, correlational and descriptive. A comprehensive review of existing literature and interviews with dental professionals were conducted to gather relevant information on the drivers and dependencies in the adoption of digital technologies in dentistry. To analyze the relationships and the dynamic structure between the variables, the MICMAC technique was used. The results of the classification showed that the key variables in the adoption of digital technologies in dentistry were technological advances in digital dentistry, clinical and aesthetic benefits, education and training, perception of risks and barriers, and integration with the clinical workflow. The MICMAC technique provided a robust and structured analytical framework to understand the interrelationships between variables and rank them based on their importance and effect on the adoption of digital technologies in dentistry.